Gene Expression and Regulation in Mammalian Cells Transcription From General Aspects - Uchiumi, Fumiaki (IntechOpen, 2018)
"Central dogma" was presented by Dr. Francis Crick 60 years ago. The information of nucleotide sequences on DNAs is transcribed into RNAs by RNA polymerases. We learned the mechanisms of how transcription determines function of proteins and behaviour of cells and even how it brings appearances of organisms. This book is intended for scientists and medical researchers especially who are interested in the relationships between transcription and human diseases. This volume consists of an introductory chapter and 14 chapters, divided into 4 parts. Each chapter is written by experts in the basic scientific field. A collection of articles presented by active and laboratory-based investigators provides recent advances and progresses in the field of transcriptional regulation in mammalian cells.